Living the RV Life : Your Ultimate Guide to Life on the Road - Bennett, Marc; Bennett, Julie (Avon, Massachusetts : Adams Media, 2018)
Both aspirational and practical, this book is your ultimate guide to living life on the road--for people of all ages looking to downsize, travel, or work on the go. Learn if life in a motor home is right for you, with insightful details on the experiences of full-time RV-ers, tips for how to choose an RV (how big? new or used?), whether to sell your home (and if not, what to do with it), model costs, sample routes and destinations, basic vehicle maintenance, legal and government considerations--and much more! Written in a light and an easy-to-understand style, this is your bible to living a mobile life.
Keywords: RV Camping; Travel guide